Kesiapan Lembaga Pendidikan Islam dalam Menghadapi Revolusi Industri 5.0: Analisis Perspektif Manajerial - G. Ginanjar Masruri; Fadhilah Anggraini Pane; Euis Erha Rohmah Hamidah; Mohamad Erihadiana (South Sulawesi Education Development (SSED), 2025)
This study aims to examine the readiness of Islamic educational institutions in facing the challenges of the Industrial Revolution 5.0, focusing on managerial aspects. The research employed a descriptive qualitative method with data collected through in-depth interviews, participatory observation, and documentation in two Islamic educational institutions with differing characteristics. The findings indicate that the understanding of school leaders and educators regarding the concept of the Industrial Revolution 5.0 remains superficial and has not been followed by adequate institutional strategic policies. The capacity of human resources, both teachers and administrative staff, is not yet optimally prepared to manage value-based technology for educational and managerial purposes. Moreover, the integration of Islamic values into the use of technology is not yet systematic and still relies on individual initiatives. These findings suggest that the readiness of Islamic educational institutions remains partial, technical, and has not reached the level of value-based managerial transformation. Therefore, strategies are needed to strengthen managerial literacy, develop sustainable human resource capacity, and integrate Islamic values into every innovation practice in education. Keywords: Islamic education management, Industrial Revolution 5.0, digital transformation, managerial literacy, Islamic value integration.